The role of probiotics in COVID-19 treatment: Gut microbiota can help physicians in the outbreak - Şahin, Mustafa (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Şahin M. The role of probiotics in COVID-19 treatment: Gut microbiota can help physicians in the outbreak. Turk J Gastroenterol 2020; 31(10): 724-5.